Optimizing crop residue-based composts for enhancing soil fertility and crop yield of rice - DADHICH, S K; PANDEY, A K; PRASANNA, R; NAIN, L; KAUSHIK, B D (The Indian Journal of Agricultural Sciences, 2012)
A field experiment was conducted using rice crop (var. Pusa Basmati1) to evaluate the effect of different crop residue based composts (prepared using pigeon pea stover, chickpea stover and mustard stover) on the post-harvest availability of macronutrients, crop growth and yields along with soil microbiological parameters. Significant enhancement in the soil microbial activity in terms of dehydrogenase and alkaline phosphatase was recorded in the pigeonpea composts amended treatments (T3) vis a vis 100% recommended dose of N and P (N120P60; T2). Grain and straw yields of rice were significantly higher in this treatment, as compared to 50% recommended dose of N and P fertilizer (N60P30). Compost application also increased the soil available P and K as compared to N60P30 indicating that compost@ 5tonnes/ha fulfils the requirement of P and K in rice crop. The observations emphasized the utility of using on-farm residues as composts as supplements with chemical fertilizers for improving soil health and plant productivity of rice crop.